2012
DOI: 10.1100/2012/793606
|View full text |Cite
|
Sign up to set email alerts
|

Removal of Pb (II) Ions from Aqueous Solutions byCladophora rivularis(Linnaeus) Hoek

Abstract: Biosorption of Pb(II) using Cladophora rivularis was examined as a function of initial pH heavy metal concentration and temperature. The optimum pH value for the biosorption of lead was 4.0. The adsorption equilibriums were well described by Langmuir and Freundlich isotherm models and it was implied by the results that the C. rivularis biomass is suitable for the development of efficient biosorbent in order to remove Pb(II) from wastewater and to recover it. The high values of correlation coefficient (R 2 = 0.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…If the sequencing results showed novel characteristics, then the Mo-reducing enzyme should have a new name, NAD(P)H: phosphomolybdate oxidoreductase or, simply, phosphomolybdate reductase. The greater understanding of the underlying mechanism of molybdenum reduction catalyzed by this enzyme could lead to improved processes in the area of bioremediation [33], reducing biocorrosion [34], biomining [35], and biorecycling of molybdenum [36, 37]. …”
Section: Discussionmentioning
confidence: 99%
“…If the sequencing results showed novel characteristics, then the Mo-reducing enzyme should have a new name, NAD(P)H: phosphomolybdate oxidoreductase or, simply, phosphomolybdate reductase. The greater understanding of the underlying mechanism of molybdenum reduction catalyzed by this enzyme could lead to improved processes in the area of bioremediation [33], reducing biocorrosion [34], biomining [35], and biorecycling of molybdenum [36, 37]. …”
Section: Discussionmentioning
confidence: 99%
“…Cladophora cell wall polysaccharides also display ion-exchange properties binding metals such as lead, copper, and zinc, and suggesting potential use of this alga in monitoring the chemical status of aquatic environments ( _ Zbikowski et al 2007), or to remove heavy metal ions from wastewater (reviewed by Mehta and Gaur 2005, Lee and Chang 2011, Jafari and Senobari 2012, Ji et al 2012 wall-binding properties, high levels of heavy metals can be toxic to Cladophora Hawkes 1986, Lamai et al 2005).…”
Section: Reproductionmentioning
confidence: 99%
“…Adsorbent that could affect the adsorption of metal ions. Functional groups like carboxyl and hydroxyl generally are used as a place for metal ions to interact so that absorption occurs (Jafari and Senobari, 2012). The FTIR spectra showed that the presence in Figure 2a.…”
Section: Characterization Of Adsorbentmentioning
confidence: 99%